Aprendizagem colaborativa para o ensino de química por meio da robótica educacional - Lima, Walex Fernandes (2016)
This master's degree dissertation intend to demonstrate the use of robotics with high school students, as well as to analyze how this technology can cooperate for the education of curricular contents related to chemistry, evidencing which one of them can be worked inside the classroom. The theoretical basis of the study is based on qualitative research, looking to make the first cycle phase of the action-research. The robotics can be seen as a tool to bring a different look at how the chemistry discipline is view in high school. This way, will be presented the construct a robotic prototype by means of the collaboration between the students, using alternative materials of low cost together with a robotics kit that uses an Open Source platform. Students of high school were voluntary in this project accomplished in the contraturn of school and had developed a mechanical prototype of a laboratory device. It must be pointed out that the ideas and the construction of the robot were accomplished by the students. The prototype developed by the students was of a mechanical stirrer for solutions. During the development of this prototype, the concept more argued between the students was about the Solutions. The development of this type of activity could generate new discussions, in pairs or groups, creating an environment that is approaching the relation between student and teacher, assisting in learning process.